The mass transfer in the capillary- porous materials - Chanh, Truong Minh (Vietnam Journal of Mechanics, 1981)
In the paper the Mass transfers in capillary-porous plate, circular cylinder are, considered within the framework of the linear isothermal generalized - diffusive theory of the homogenous fluid mixtures. Solutions are obtained by the method of laplacces integral transformation.